2020
DOI: 10.1039/c9fo03015h
|View full text |Cite
|
Sign up to set email alerts
|

Vinegar extract ameliorates alcohol-induced liver damage associated with the modulation of gut microbiota in mice

Abstract: Vinegar extract inhibited alcohol-induced ROS generation and inflammation. Vinegar extract modulated gut microbiota and improved intestinal homeostasis, which could be used as a novel gut microbiota manipulator against alcohol-induced liver damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 54 publications
6
26
0
Order By: Relevance
“…A previous study also demonstrated that stress and infection could result in a significant decrease in the SCFA-producing genera, such as Butyricimonas , Anaerostipes , Butyricicoccus , Coprococcus , and Parabacteroides [ 48 ]. Akkermansia and Lactobacillus showed a significant positive correlation with intestinal tight junction proteins and a negative correlation with inflammation and oxidative stress [ 49 ]. The triathletes participate in extremely high-intensity triathlon competition, and follow daily programmed training for higher sports-related physical fitness.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also demonstrated that stress and infection could result in a significant decrease in the SCFA-producing genera, such as Butyricimonas , Anaerostipes , Butyricicoccus , Coprococcus , and Parabacteroides [ 48 ]. Akkermansia and Lactobacillus showed a significant positive correlation with intestinal tight junction proteins and a negative correlation with inflammation and oxidative stress [ 49 ]. The triathletes participate in extremely high-intensity triathlon competition, and follow daily programmed training for higher sports-related physical fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the H-Mg group presented a significant increase of Butyricimonas and Parabacteroides. Recently, Xia et al negatively correlated Proteobacteria, Butyricimonas, Parabacteroides, and Bilophila abundance with liver inflammation and intestinal epithelial claudin expression [33]. Moreover, Victivallis and Butyricimonas abundance have been positively correlated with hepatic lipid accumulation [34].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we could preliminarily deduce the CCP could adjust the changes of two main phyla to produce prebiotic-like effects [22][23][24]. Verrucomicrobia was considered as a probiotic, which showed a negative correlation with hepatic inflammation and oxidative stress [25,26]. Especially, Akkermansiaceae, the most representative gut microbe in the Verrucomicrobia, could prevent the weight gain caused by a high-fat diet, repair the damaged integrity of the intestinal epithelium barrier, reduce endotoxin levels in the blood, and improve insulin resistance [27,28].…”
Section: Discussionmentioning
confidence: 99%